2019
DOI: 10.3390/app9112277
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study of a Novel Piezo MEMS Tweezer for Soft Materials Characterization

Abstract: The opportunity to know the status of a soft tissue (ST) in situ can be very useful for microsurgery or early diagnosis. Since normal and diseased tissues have different mechanical characteristics, many systems have been developed to carry out such measurements locally. Among them, MEMS tweezers are very relevant for their efficiency and relative simplicity compared to the other systems. In this paper a novel piezoelectric MEMS tweezer for soft materials analysis and characterization is presented. A theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Finally, a significant part of modern surgery relies on pioneering efforts to bring about advances in nano and microengineering to the lab and surgical activities. In this issue, an example of extreme miniaturization of the tools used in surgery has been provided by two papers, one concerning the development of a new piezo MEMS tweezer for soft materials characterization [32] and one describing some reasonable progress of MEMS for operations in a surgical scenario [33].…”
Section: About the Present Issuementioning
confidence: 99%
“…Finally, a significant part of modern surgery relies on pioneering efforts to bring about advances in nano and microengineering to the lab and surgical activities. In this issue, an example of extreme miniaturization of the tools used in surgery has been provided by two papers, one concerning the development of a new piezo MEMS tweezer for soft materials characterization [32] and one describing some reasonable progress of MEMS for operations in a surgical scenario [33].…”
Section: About the Present Issuementioning
confidence: 99%
“…It can be shown that parasitic deformations are minimized when the curved beam elastic weights center is overlapping with the center of the conjugate profiles. The CSFH was adopted in several microdevices, such as in micromanipulators [3], micro mechanisms, grippers [4], microtribometers, etc. These microsystems can be actuated by means of electrostatic actuators, such as linear or rotary comb drives, but the robustness and feasibility of such components in static and as well as dynamic conditions still raises some concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-tweezers are fundamental manipulators in nano- and biotechnology developed to accurately manipulate and localize objects such as nano-particles, blood cells, and DNA strands (Yang and Xu, 2017). These devices can be operated by using different actuation techniques such as electrostatic (Alneamy et al, 2020; Farrokhabadi et al, 2015), magnetic (Kang and Xu, 2020), piezoelectric (Botta et al, 2019), electrothermal (Solano and Wood, 2007), and optoelectronic (Chiou et al, 2005; Elvira et al, 2018). Although nano-tweezers have been developed in recent years, the use of these vital tools in trapping biological components to study and modify them is still one of the most challenging and motivating interdisciplinary fields (Jiang et al, 2021; Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%